Improved sample preparation using bead mill homogenization - Madison E. Walbrun; Aamna Aijaz; Gabriella Ryan; John D. Bunting; Zachary P. Morehouse; Rodney J. Nash (Advances in Sample Preparation)
Proper sample preparation is the key to having successful data analysis downstream. Despite the many efforts to improve sample preparation, there are still many inconsistencies and challenges when attempting to produce a sample for downstream analysis. Here we compare common methods used in sample preparation (detergent and manual Dounce homogenization) to mechanical Bead Mill homogenization. These methods have been shown to lyse both cell and tissue, however, concentrations and detectability of desired analytes can be greatly reduced. These results show that mechanical Bead Mill homogenization requires less starting sample, and less time, while producing higher protein concentrations with increased reproducibility, therefore improving downstream analysis.